PERMAINAN INOVASI ENGKLE GEOMETRI UNTUK MENGEMBANGKAN KREATIVITAS ANAK USIA 5-6 TAHUN DI RA AL-MUSTAQIM BRINGIN BENDO SIDOARJO - Ahmad Fachrurrazi; Anis Rahmana (Jurnal Al-Fatih, 2025)
The innovation game of geometric engkle is a modified game. This game can develop children's creativity. Creativity is very important for the development stage, because it has a good level of creativity. Then the child will be easier to solve the problems that occur to him. Because creative children have various ideas in themselves. This study aims to determine whether the Overview of the innovation of the geometric engkle game can develop the creativity of children aged 5-6 years. The method used is Descriptive Qualitative. The subjects of the study were 5 children of Kindergarten B. Using primary data with observation, interview, and documentation methods. The results of the study showed that the innovation game of geometric engkle succeeded in developing children's creativity. Children become better at producing new images and can recognize geometric shapes and colors correctly. This game is very effective in stimulating children's thinking skills. The researcher gave a suggestion. To teachers to make more efforts in learning activities related to traditional games in ancient times and combine the level of creativity possessed by each child. Because with monitoring, we as teachers can find out the development of their creativity.